Perception of Global Participants of ITEC Nations on Country's Preparedness and Response to COVID-19 Pandemic - Upadhyay, Kritika; Goel, Sonu; Soundappan, Kathirvel (Frontiers in Public Health, 2022)
Background The Coronavirus disease 2019 (COVID-19) pandemic has exposed the public health preparedness and response system across the world. The current study was conducted to gauge the perception of public health professionals of Indian Technical and Economic Cooperation (ITEC) countries regarding the preparedness and responses of their countries in mitigating the COVID-19 pandemic. Methodology Three capacity-building programs, namely “Managing COVID-19 Pandemic–Experience and Best practices of India” were conducted by PGIMER, Chandigarh, for public health professionals from ITEC countries from April to May 2021 in which 97 participants from 13 countries have participated. The tools used in the study were adapted from WHO's COVID-19 Strategic Preparedness and Response (SPRP), Monitoring and Evaluation Framework, interim guidelines for Critical preparedness, readiness and response actions for COVID-19, and a strategic framework for emergency preparedness, and finalized using Delphi technique. The overall preparedness of managing COVID-19 was rated using five-point Likert scale, whereas the overall score for the country in combating the COVID-19 pandemic was assessed using 10 point scale. Results We found that the perception of public health professionals to government response regarding COVID-19 for fostering improvement on COVID-19 situation was “moderate” with respect to transmission and surveillance mechanism, uniform reporting mechanism, and availability of adequate personal protective equipment (PPE) for health workers. However, the participants rated government response as “poor” in the availability of multisectoral national operational plan, human resource capacity, availability of trained rapid response team (RRT), preparedness in prevention and clinical management, training of healthcare workers, communication and community engagement strategies, facilities to test samples of patients, and transparent governance and administration. Conclusion A poor level of preparedness of countries in diverse domains of managing the COVID-19 pandemic was observed. As the global threat of COVID-19 is still looming, great efforts on building a robust preparedness and response system for COVID-19 and similar pandemics are urgently required.